It's the law - Furris, Nicholas J.; Hackney, Gary.; Simpson, Deborah; Spanos, Staci; Cambridge Educational (Firm); Digital Vision Works; Films for the Humanities (Lawrenceville, NJ : Cambridge Educational, 2001)
The laws of the criminal justice system are framed first and foremost by the United States Constitution, the document that gives our government its powers, limits those powers, and ensures our rights to life, liberty, andproperty. While the system is designed to bring criminals to justice, it must also meet the standards of due processset forth in the Constitution. The criminal justice system,then, has two functions: protect the public safety and maintain the public confidence. In this program, lawyers, prosecutors, and judges explain the differences between misdemeanors, felonies, the various degrees of crimes, and the elements of a crime. Investigation procedures in the gathering of evidence and statements are discussed. Legal experts and police officers clearly illustrate such concepts as 5th Amendment rights, Miranda warnings, the'stop and frisk' rule, search warrants, and the'knock and announce' rule. Probable cause and arrest procedures are also demonstrated.
Executive producer, Charlotte Angel ; editor, Mark Garrett ; directory of photography, Patrick Herbert.
Narrated by Staci Spanos.
Keywords: Crime -- United States; Criminal justice, Administration of -- United States; Criminal law -- United States